Research and development projects at ACUINOVA on fish and shrimp nutrition - López Fernández A. (Feeding tomorrow's fish, 1997)
ACUINOVA is a company involved in marine aquaculture, owned by the PESCANOVA group; the latter being one of the largest fishing companies in the world and very important in the food sector. ACUINOVA was established in 1986 and since then has been developing a 'strategic plan' with the aim of controlling the production process involved in the culture of different marine species, the ultimate aim being to complement the supply of marine fisheries products that currently depend to a great extend on capture fisheries. When we talk about 'production process control' we mean every part of the process, from those related to the design of facilities to such as cost control, quality control, culture technology, nutrition, pathology, genetic improvement, as well as the commercialisation of the final products. The more control we establish in our culture method, the less it is influenced by external agents or, at least, those influences can be minimized. This lead us to the possibility of developing an 'intensive farming system'. Consequently, since nutrition plays a major and critical role in intensive farming systems, the need for a 'Nutrition subproject' arose. The aim of the subproject was to guarantee not only the adequate food supply for a certain set of conditions but also to develop simultaneously along with any progressive changes, that may be introduced into the system. This means that it must be able to produce a 'tailored food'. The strategic plan of ACUINOVA de Galicia is currently focused on the production of sea bream (Sparus aurata) fry and the ongrowing of turbot (Scophthalmus maximus), whereas that of ACUINOVA de Andalucía is focused on integrated shrimp farming (Penaeus japonicus). The current paper summarizes ACUINOVA's evolution, progressive advances and achievements in this field including its medium-term strategies.
Workshop of the CIHEAM Network on Technology of Aquaculture in the Mediterranean (TECAM), 1996/06/24-26, Mazarrón (Spain)